Layout Criteria for Enhancing Indonesian SMEs Production’s Performance - Azis, Anton Mulyono (International Journal of Emerging Trends in Social Sciences, 2018)
A reliable layout will improve the process effectiveness and lead the production performance at an excellent level. Unfortunately, SMEs in Indonesia have not realized how important it is, and put layout decisions just as an alternative operating decision to improve company’s performance. This study aims to identify reliable layout criteria that should be applied by SMEs production managers in Indonesia to improve their production performance. This research used quantitative methods by investigating 276 SMEs in West Java – Indonesia. The result found that related to the layout design; technology, process, facilities, and product type are the most important factors affecting company’s production performance. The four factors are then derived into appropriate criteria that can be applied to Indonesian SMEs. Two kinds of further research can be continued by deepening each of the generated criteria and their application in the specific SME so that the results will better reflect the conditions of SME’s production layout in Indonesia.